Students’ Perception of Supporting Factors during Remote English Teaching - Made Emi Anggreyani; Kadek Sintya Dewi (Universitas Pendidikan Ganesha, 2023)
The covid-19 pandemic has made the traditional learning system distance learning. Some research outside the Indonesian context states that distance learning has become commonplace, but it is different from Indonesia. So that the supporting factors faced by students in carrying out remote teaching are different, especially in the Indonesian context. Since remote teaching was implemented, there have been many obstacles experienced by teachers and students in following the learning process. This study aims to analyze students' perceptions regarding the supporting factors for the implementation of remote teaching. This study uses mixed methods (qualitative and quantitative) which aims to analyze more valid and accurate data results. The focus of this research is 142 eleventh grade students who have carried out remote teaching. In data collection, researchers conducted literature studies, interviews and questionnaires. The results of this study show that there are ten factors supporting the implementation of distance learning found in the matrix literature review and confirmed by the subject. The supporting factors found can be used as guidelines for the government, teachers and students in implementing the distance learning process in the future.